THE INFLUENCE OF THE RUSSIAN EMPIRE ON THE ECONOMY OF AFGHANISTAN AND ITS CONSEQUENCES (Eureka Journal of Business, Economics & Innovation Studies, 2026)
This article examines the significant role Russian Empire on the economy of Afghanistan. In the second half of the nineteenth century and the early twentieth century, Afghanistan’s economy became a region where the interests of major powers, primarily the Russian Empire and Great Britain. The strengthening of the Russian Empire’s military and political position in Central Asia led to a gradual expansion of its economic relations with Afghanistan. This process had both direct and indirect impacts on Afghanistan’s economic structure, bringing about notable changes in the country’s foreign trade orientation, market relations, and forms of production.
Keywords: Russian Empire, Afghanistan economy, “soft power”, V. N. Zvonko, I. S. Grebenshchikov, Habibullah Rafi, Angus Hamilton, T. Hakimov, Fayz Muhammad Katib, “geo-economic diplomacy”.